2020
DOI: 10.1093/femsre/fuaa052
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite relationship between gut microbiota, intestinal mucus and dietary fibers: towards preventive strategies against enteric infections

Abstract: The human gut is inhabited by a large variety of microorganims involved in many physiological processes and collectively refered as to gut microbiota. Disrupted microbiome has been associated with negative health outcomes and especially could promote the onset of enteric infections. To sustain their growth and persistence within the human digestive tract, gut microbes and enteric pathogens rely on two main polysaccharide compartments, namely dietary fibers and mucus carbohydrates. Several evidences suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 444 publications
0
26
0
Order By: Relevance
“…We argue that this positive effect on pathogen growth may not be an issue in the context of the complex nutritional and microbial background of the distal small intestine, the main site of ETEC colonization [ 3 , 4 , 86 , 87 , 88 , 89 ]. In the human gut, fibers are degraded into smaller carbohydrates by the endogenous gut microbiota, providing substrates for pathogens, such as ETEC, which generally behave as secondary degraders [ 90 ]. By performing fecal batch experiments including microbiota from human origin, we confirmed that dietary-fiber-containing products had no significant effect on ETEC colonization in a complex microbial environment, with only a slight tendency of yeast cell walls to reduce pathogen levels in both the luminal and mucosal compartments.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that this positive effect on pathogen growth may not be an issue in the context of the complex nutritional and microbial background of the distal small intestine, the main site of ETEC colonization [ 3 , 4 , 86 , 87 , 88 , 89 ]. In the human gut, fibers are degraded into smaller carbohydrates by the endogenous gut microbiota, providing substrates for pathogens, such as ETEC, which generally behave as secondary degraders [ 90 ]. By performing fecal batch experiments including microbiota from human origin, we confirmed that dietary-fiber-containing products had no significant effect on ETEC colonization in a complex microbial environment, with only a slight tendency of yeast cell walls to reduce pathogen levels in both the luminal and mucosal compartments.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of dietary fibers on human health is now well acknowledged, but their ability to exert antagonistic effects against enteric pathogens remain poorly studied [7,36,[45][46][47]. To date, the vast majority of studies investigating the potential of fibers in the fight against ETEC-associated infections have been performed on porcine ETEC strains [48][49][50][51][52], while studies involving ETEC strains from human origins are scarce [28,29,53].…”
Section: Discussionmentioning
confidence: 99%
“…Insoluble dietary fiber particles have even been recently shown to constitute a microbiota niche on their own [5,6]. Another understudied effect of dietary fibers is their ability to prevent enteric infections [7]. Scarce in vitro studies have already shown the antagonistic properties of fibers against various enteric bacterial pathogens, mostly through a direct bacteriostatic effect, anti-adhesion properties on intestinal cells [8][9][10][11] or a decoy for pathogen/toxin binding to mucosal polysaccharides [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…109 Increased availability of these free sugars in the intestinal lumen is made possible by the presence of saccharolytic Bacteroides thetaiotaomicron, on which C difficile and S typhimurium rely. 110 By the preceding, exploiting these molecules derived from the microbiota as both signals and nutrients remains critical for the hosts' pathogenic bacterial infection. Although such organisms have developed many strategies of circumventing the resistance to colonization given by the microbiota, and in other situations even employ its help, the microbiota offers repulsion and thus creates intense competition for resources.…”
Section: Detrimental Effects Of the Gut Microbiome In Inducing Colitismentioning
confidence: 99%